Histologic Findings of Severe/Therapy-Resistant Asthma From Video-assisted Thoracoscopic Surgery Biopsies. (February 2017) - Trejo Bittar, Humberto E.; Doberer, Daniel; Mehrad, Mitra; Strollo, Diane C.; Leader, Joseph K.; Wenzel, Sally; Yousem, Samuel A.
Abstract : The histologic changes occurring in severe/therapy-resistant asthma (SA) as defined by the European Respiratory Society/American Thoracic Society guidelines, particularly at the level of the distal airways are unknown. This study describes the clinical, radiologic, and histologic characteristics of 29 SA patients who underwent video-assisted thoracoscopic surgery lung biopsy. Pathologic observations were correlated with clinical features, especially the presence of autoimmune disease (AID) (15/29, 51.7%). Ten biopsies (10/29, 34.5%) showed only small airway manifestations of asthma, whereas in 19 (65.5%) asthmatic granulomatosis, manifested by asthmatic bronchiolitis supplemented by an alveolar septal mononuclear infiltrates with non-necrotizing granulomas, was present. SA patients without asthmatic granulomatosis showed more striking small airway injury, subbasement membrane thickening, and neutrophilic infiltrates. Cases with concurrent AID had a tendency to more parenchymal eosinophilic inflammation, more bronchiolocentric granulomas, and a suggestion of increased responsivity to nonsteroidal immunosuppressive therapy. Histologic examination of video-assisted thoracoscopic surgery lung biopsies in SA demonstrates diverse pathologies including cases associated with granulomatous inflammation in addition to eosinophilic infiltrates. This spectrum of histologies may link to a high incidence of AID.